Digitalization of banking business - Bai Xianyu (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the process of credit risk management in the system of ensuring the bank's financial stability. The subject of research is is the modern methods of assessing credit risk levels and managing them within the system of ensuring the bank's financial stability. The purpose of the qualifying master's thesis is to summarize the theoretical foundations of organizing credit risk management to ensure the financial stability of the bank. Based on the results of the research, theoretical and practical provisions are formulated, which the author has developed into specific proposals for improving the credit risk management system to ensure the financial stability of banks. The obtained results can be used to calculate credit risk levels and evaluate the quality of credit portfolio management, ensuring financial stability and minimizing credit risks.
Діджиталізація банківського бізнесу
Scientific adviser: Samorodov Borys, doctor of economics, professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; credit risks; financial stability; credit portfolio; PrivatBank; risk management